Local Molecular Reactivity of the Colored Dansylglycine in Water and Dioxane Studied through Conceptual DFT - Juan Frau; Daniel Glossman-Mitnik (Journal of Chemistry)
This study evaluated a fixed long-range corrected range-separated hybrid (RSH) density functional associated with the Def2TZVP basis set alongside the SMD solvation model for the computation of the structure, molecular properties, and chemical reactivity of the M8 intermediate melanoidin pigment in the presence of water and dioxane. The preference of the active sites pertinent to radical, nucleophilic, and electrophilic attacks is made through linking them with the electrophilic and nucleophilic Parr functions, Fukui function indices, and condensed dual descriptor which are chemical reactivity descriptors that arise from conceptual density functional theory. The study confirmed the results from previous works showing that the MN12SX density functional is the most appropriate in predicting the chemical reactivity of this molecule in both solvents.